The Strategy of Street Vendors in Increasing Income at Lakota Beach, Tomia District, Wakatobi Regency According to Sharia Economics - Ardiansyah, Ardiansyah; Aslan, La Ode (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to examine the strategies employed by street vendors at Lakota Beach, Tomia District, Wakatobi Regency, analyze their income, and understand the application of income-increasing strategies based on Sharia Economic principles. The type of research used is field research with a qualitative descriptive approach. Data were collected through observation, interviews, and documentation, involving both primary and secondary data sources at the research site. The results of the study indicate that the strategies implemented by street vendors at Lakota Beach are considered effective, as evidenced by their ability to maintain product quality, set fair prices, carry out targeted promotions, choose strategic locations, and provide excellent service. These factors create significant opportunities for vendors to survive and thrive amid intense business competition. In addition, the vendors’ income has increased significantly due to good management practices, the use of technology for promotion, and their willingness to seize opportunities such as fulfilling large-scale orders. From the perspective of Sharia Economics, the income-boosting strategies adopted by the street vendors also prioritize principles such as honesty in transactions, maintaining product quality and halal standards, showing friendliness and patience, and building customer loyalty. These principles serve as key factors in the vendors’ success in growing their businesses and achieving sustainable income growth.